Deficits in Behavioral Functions of Intact Barrel Cortex Following Lesions of Homotopic Contralateral Cortex - Chaudhary, Rahul; Rema, V. (Frontiers in Systems Neuroscience, 2018)
Bilateral inputs, processed by interhemispheric interactions, play an important role in a wide variety of integrated behavioral functions during the performance of auditory, visual or sensorimotor tasks. Stroke-like injuries are known to cause dysfunctions in performance of bimanual tasks that depend upon bilateral interactions. Although unilateral focal injury to the somatosensory cortex is known to modify neuronal activity and experience-dependent plasticity in the intact contralesional hemisphere, the long-term deficits at a behavioral level are not well understood. We investigated the effects of unilateral lesions of the somatosensory cortex on the performance of a sensory behavior which was acquired with bilateral sensory inputs. We trained adult rats to perform a whisker-dependent tactile behavior using whiskers on both sides of the face. Unilateral lesions of the whisker barrel cortex resulted in persistent impairments in the whisker-dependent sensory behavior of the contralesional cortex. These deficits were specific to performance of the task at the highest levels of sensitivity. Comparable deficits were observed in bilaterally trained normal rats when they performed the task with only one set of whiskers. These results suggest that dynamic interaction of bilateral activity-driven inputs to homotopic areas of the cerebral cortex may be necessary for optimal performance of a sensory behavior that was learned using bilateral sensory inputs. The prolonged impairment in execution of the learnt task by rats following unilateral lesions of somatosensory cortex could specifically be due to the absence of active interactions with the lesioned cortex. Thus many of the behavioral deficits seen in humans with brain injury could be a result of compromised bilateral information processing in the cortex.